Suggestive Connotation In The Narrations Of Imam Ali Bin Muhammad Al-Hadi (Peace Be Upon Him) In Light Of Cognitive Linguistics - المنكوشــي علــي مـيران جبــار (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
This research addresses the phenomenon of suggestive meaning, the linguistic concept of which originated in cognitive linguistics. This concept has a prominent feature in contemporary linguistics. Suggestive meaning is characterized by its possession of similar procedures and knowledge directed toward the process of producing the meaning of linguistic expression, with its meanings and purposes varying according to its users, whether through the phonetic, morphological, syntactic, or lexical influence of the linguistic term , The central meaning in the linguistic structure and the suggestive meaning in the marginal or added sense to that structure and branching from it, meaning that the meaning of what comes out of the understanding as a mental image explains that structure and places it in an environment from which that same meaning is presented for acceptance and conditional on perception; thus it is considered a shared social phenomenon and not an individual dynamic process, and the mental structures themselves control perception and thus establish the linguistic system, This is what (Jackendoff) sees as the levels of mental representation of the linguistic structure being completely in harmony with the linguistic system surrounding it that achieves a comprehensive linguistic theory, and the words of the infallible Imam are nothing but an important step in investing linguistic and linguistic effort and also a fruit of the fruits of cognitive and cultural communication despite the abundance of beliefs and the consolidation of heavenly values and the completion of life and legislative functions in achieving the principles of the Holy Qur’an and the pure prophetic Sunnah, Therefore, which aimed to research its journey from the aspects of the mechanisms used for the cognitive linguistic theory, relying on studying the speeches of the Imam (peace be upon him) to the recipient, and to place most of my attention on studying the suggestive meaning that achieves its acceptance by the recipient.